THE EFFECT OF PSYCHOLOGY FACTORS TOWARD E-COMMERCE PURCHASE DECISION - Rani Raharjanti (International Conference on Industrial Revolution for Polytechnic Education, 2019)
The aim of this research is to analyze and to test about the effect of trust, service quality, and risk perception toward purchase decision e-commerce transaction. The output of this research is to figure out psychology factors influence purchase decision and an article about this. The population of this research were Accounting departement’s student of Politeknik Negeri Semarang. Purposive sampling was used on this research. Data was collected from students through questionnaires. Validity and reliability tests were used to test valid and reliable distributed questionnaires. We used a t test to test the hypothesis where the level of significance is 5% with a two-tailed hypothesis test. Based on the results of the analysis, it was concluded that the trust variable proved have a positive influence towards purchasing decisions in e-commerce transactions, meaning that the higher of the level of trust, the higher the purchasing decision in e-commerce transactions. While service quality and risk perception are empirically proven have no influence on e-commerce purchasing decisions. This is because consumers feel that almost every e-commerce has the same quality of service and risk management, so consumers are no longer too worried about these two problems